The color management handbook for visual effects artists : digital color principles, color management fundamentals & ACES workflows - Perez, Víctor (Film director), ....- (New York. NY : Routledge, 2023)
"Victor Perez brings together the research and expertise of world-leading color scientists, to create a comprehensive guide for VFX Artists in Color Management. The book explores the latest standards of HDR and ACES workflows, in an easily digestible and widely applicable resource. Its purpose is to make artists confident and familiar with Color Management and its science, to improve the quality of visual effects worldwide. Without assuming any previous knowledge, this self-contained book builds the readers understanding from the ground up, exploring all the elements of the Color Workflow at a scientific level. It covers how to setup a consistent pipeline in relation to other departments, inside and outside visual effects, from camera to screen, so everybody is aligned to the same standards, preserving color qualities, consistency, and maintaining the artistic intent end to end. It also delves into all the integral concepts for color management, ranging from Color Theory to Digital Image Fundamentals, and much more. This book is an invaluable resource for VFX students and professionals who want to be well-informed of the latest HDR and ACES pipelines, as well as those at every level of production, wishing to gain a deeper understanding of managing color in visual effects projects"
Keywords: Cinematography; Color management